Ascertainment of Aspirin Exposure Using Structured and Unstructured Large-scale Electronic Health Record Data. Issue 10 (October 2019) - Bustamante, Ranier; Earles, Ashley; Murphy, James D.; Bryant, Alex K.; Patterson, Olga V.; Gawron, Andrew J.; Kaltenbach, Tonya; Whooley, Mary A.; Fisher, Deborah A.; Saini, Sameer D.; Gupta, Samir; Liu, Lin
Abstract : Background: Aspirin impacts risk for important outcomes such as cancer, cardiovascular disease, and gastrointestinal bleeding. However, ascertaining exposure to medications available both by prescription and over-the-counter such as aspirin for research and quality improvement purposes is a challenge. Objectives: Develop and validate a strategy for ascertaining aspirin exposure, utilizing a combination of structured and unstructured data. Research Design: This is a retrospective cohort study. Subjects: In total, 1, 869, 439 Veterans who underwent usual care colonoscopy 1999–2014 within the Department of Veterans Affairs. Measures: Aspirin exposure and dose were obtained from an ascertainment strategy combining query of structured medication records available in electronic health record databases and unstructured data extracted from free-text progress notes. Prevalence of any aspirin exposure and dose-specific exposure were estimated. Positive predictive value and negative predictive value were used to assess strategy performance, using manual chart review as the reference standard. Results: Our combined strategy for ascertaining aspirin exposure using structured and unstructured data reached a positive predictive value and negative predictive value of 99.2% and 97.5% for any exposure, and 92.6% and 98.3% for dose-specific exposure. Estimated prevalence of any aspirin exposure was 36.3% (95% confidence interval: 36.2%–36.4%) and dose-specific exposure was 35.4% (95% confidence interval: 35.3%–35.5%). Conclusions: A readily accessible approach utilizing a combination of structured medication records and query of unstructured data can be used to ascertain aspirin exposure when manual chart review is impractical. Abstract : Supplemental Digital Content is available in the text.